Metode Pendidikan Akhlak dalam Kitab Al Akhlak Li Al Banin Jilid 1-2 Karangan Syaikh Umar Baraja - Adib, Hamdan (Ngaji: Jurnal Pendidikan Islam, 2021)
The purpose of this study is to determine the methods of moral education in the book Al-Akhlak Li Al Banin Volume 1-2 by Shaykh Umar Baraja. Where morals are very urgent at this time. The urgency of moral education as a solution to current problems can be seen with the implementation of the 2013R curriculum in the world of education. but this is not yet the right solution that can change the morals of children, especially instantaneously. Collaboration between schools, communities and especially parents is required. Parents are the main elements in carrying out moral education. The research method used is library research with the analysis technique is content analysis. The results obtained are the method of moral education in the translation of Al-Akhlak Li Al Banin volumes I and II by Shaykh Umar Baraja, which is carried out in three forms: First, direct communication methods Second, the method of guidance with advice. Third, the method of guidance with practice or habituation. The rationale for moral education is Al-Qur'an and Hadith. Al-Qur'an and Hadith have always been used as guidelines for the teachings of Islam. The concept of children's moral education in the translation of Al-Akhlak Li Al Banin Volume 1-2 by Shaykh Umar Baraja is to have good morals since childhood, familiarize oneself with good morals, examples of bad morals, the obligation to glorify Allah SWT, the obligation to glorify the prophet. muhammad saw, manners to people, children who do not have manners, have a trustworthy nature (can be trusted), carry out an attitude of obedience.   Abstrak: Tujuan penelitian ini untuk mengetahui metode pendidikan akhlak yang ada dalam kitab Al-Akhlak Li Al Banin Jilid 1-2 Karya Syaikh Umar Baraja. Dimana akhlak merupakan hal yang sangat urgen saat ini. Urgensi pendidikan akhlak sebagai solusi permasalahan saat ini terlihat dengan diberlakukanya kurikulum 2013R dalam dunia pendidikan. namun ini belumlah solusi jitu yang bisa merubah akhlak anak khususnya dengan instan. Diperlukan kerjasama antar sekolah, masyarakat dan khususnya orang tua. Orang tua merupakan elemen pokok dalam melaksanakan pendidikan akhlak. Metode penelitian yang digunakan adalah library research dengan teknik analisisnya adalah konten analisis. Hasil yang di dapatkan yaitu metode pendidikan akhlak di dalam kitab terjemahan Al-Akhlak Li Al Banin Jilid I dan II  karya Syaikh Umar Baraja dilaksanakan dalam tiga bentuk yaitu Pertama, metode komunikasi langsung. Kedua, metode bimbingan dengan  nasihat. Ketiga, metode bimbingan dengan latihan atau pembiasaan. Dasar pemikiran pendidikan akhlak adalah Al-Qur’an dan Hadist. Al-Qur’an dan Hadist selalu dijadikan sebagai perdoman ajaran agama Islam. Konsep pendidikan akhlak anak dalam kitab terjemahan Al-Akhlak Li Al Banin Jilid 1-2 karya Syaikh Umar Baraja adalah mempunyai akhlak yang baik sejak kecil, membiasakan diri dengan akhlak yang baik, contoh akhlak yang tidak baik, kewajiban mengagungkan Allah swt, kewajiban mengagungkan nabi muhammad saw, sopan santun kepada orang, anak yang tidak punya sopan santun, memiliki sifat amanah (dapat dipercaya), melaksanakan sikap ta’at. Kata Kunci: Metode, Pendidikan Akhlak, Al Akhlak Li Al Banin